(untitled) (Journal of the Management Sciences, 2024)
The study examined the determinants of capital structure and debt of consumer goods manufacturing companies in Nigeria. Ex Post facto research design was adopted for the study. A sample size of eighteen (18) quoted consumer goods manufacturing companies were selected from a population of 20 companies. Data were extracted from the annual reports and accounts of the sample’s companies from 2011 to 2022. Regression analysis was employed to test the hypotheses via E-view 9.0. Based on the analysis of data, the study found that liquidity has negative significant on debt of consumer goods manufacturing companies in Nigeria, whereas age of company has a positive insignificant effect on debt of consumer goods manufacturing companies in Nigeria. The study recommended among others that Management should maintain an optimal balance between current assets and current liabilities. If the liquidity is too high (current assets is much higher than current liabilities).